A descriptive system for the Infant health-related Quality of life Instrument (IQI): Measuring health with a mobile app. - Ruslan Jabrayilov (PLoS ONE, 2018)
BACKGROUND:The assessment of health-related quality of life (HRQoL) is important for health outcomes research, disease modeling studies and comparisons of different healthcare interventions. Yet, only a few tools are available to assess HRQoL in 0-1-year-old infants. Furthermore, there is a need for an instrument able to assess HRQoL with a single, standardized, overall score in the first year of life. Here we described the development of the Infant health-related Quality of life Instrument (IQI), a generic, preference-based instrument that can be administered through a mobile application for assessing HRQoL in 0-1-year-old infants. METHODS:A multi-step development process began by extracting candidate health concepts from relevant measures identified by two literature searches. Next, three panels, with experts from Asia, Europe, New Zealand and United States of America, and two surveys, with primary caregivers in New Zealand, Singapore, and the United Kingdom, evaluated the relevance of the candidate health concepts, organized them into attributes based on their similarities, explored alternative attributes and generated response scales. Additional interviews assessed the cross-cultural interpretability, parents' understanding of health attributes, and the usability of the mobile application. RESULTS:The final list of 7 health attributes included in the IQI consisted of sleeping, feeding, breathing, stooling/poo, mood, skin, and interaction. The users' experiences with the mobile application were generally positive. CONCLUSIONS:The IQI is the first generic, preference-based, instrument designed to assess overall HRQoL in 0-1-year old infants. It is short and easy-to-administer through a mobile application. Moreover, close attention was paid to the opinions of the infants' primary caregivers during the instrument and mobile application development process.